Streptococcus pneumoniae infection increases expression of von Willebrand factor (vWF) in a mouse brain endothelium model - Nurul Adhwa Rahman,; SuwarnI D,; Siti Hanna M, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
von Willebrand factor (vWF) is a large multimeric glycoprotein which is normally released by the brain endothelial cells and is therefore present as a circulating protein in the blood. The initial and mature structure of vWF is uncleaved; however, pneumococcal infection can cause the cleavage of the protein, thus formingseveral multimers at different sizes. The present study tested the hypothesis that Streptococcus pneumoniae infection of brain endothelial cells in culture induces the release of vWF at certain sizes time-dependently. Immortalized mouse brain endothelial cells (bEnd.3) were infected at specific hours with Streptococcus pneumoniae strains (serotype 19F). Immunofluorescence microscopy was performed and quantified accordingly. Cells were also extracted, and the proteins were separated into different sizes by western blot. The expression of vWF was then analysed and compared for a potential relationship between the strains and between the specific time of infection. The expression of vWF was elevated during infection. Even though multiple and non-specific events can also cause the cleavage of vWF, this study showed that the cleavage pattern of vWF is potentially dependent on the incubation time of infection.